Implementasi Pembelajaran Metode Seven Jumps Berbasis Model Theory Of Planned Behavior (TPB) Dalam Pencegahan Perilaku Seksual Pada Remaja Putri - Dwi Purwanti; Suparji Suparji (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2020)
Background: Sexual behavior is increasingly prevalent in teenagers with various consequences, one of which is teenage pregnancy. The impact of pregnancy, namely family disgrace, social exclusion, unwanted pregnancy sometimes ends in abortion which can lead to death, sexually transmitted disease HIV-AIDS. Lack of nformation and misconceptions about sexual behavior that they get from various media, try and have bad consequences. Various methods are used to provide understanding to adolescents, one of which is by learning the seven jumps method, learning based on problems by paying attention to several background aspects that influence the occurrence of this behavior. This study aims to develop a learning method of the seven jumps based on Theory of Planned Behavior (TPB) on the prevention of sexual behavior in young girls at SMK Dr. Soetomo Surabaya. Methods: This type of research was analytic observational, with cross sectional design. The population of the research was that of class XII and class XI girls at SMK Dr. Soetomo Surabaya, with a population size of 320. The sample size in the study was determined by the Rule of the Thumb formula, the sample size was 210 students. The independent variable in this research were seven jumps; theory of planned behavior and prevention of sexual behavior was the dependent variable. Collecting data using a questionnaire. Descriptive data analysis and inferential analysis with PLS (Partial Least Square) (factor loading ≥0.5 and t >1.96) Results: There was an influence of Social Factors on Perceived Behavior Control, Personal factors on Attitude Toward Behavior, Personal factors on Perceived Behavior Control, Personal Personal factor towards Subjective Norms, Information factor on Attitude Toward Behavior, Information factor on Perceived Behavior Control, Attitude Toward Behavior against seven jumps, Perceived Behavior Control against Seven Jumps, Subjective Norm against Seven Jumps, Seven Jumps on Intention of Sexual Behavior (t ˃1.96), and there was no influence of social factors on Subjective Norms, Social factors on Attitude Toward Behavior Information on Subjective Norms (t ≤1.96) Conclusion: background variables personal factors, social factors and information factors adhere to the three variables attitude behavior control, subjective norm and Perceived behavior control, while the three variables will affect the implementation of the seven jumps method, and the seven jumps will affect the intense prevention of sexual behavior. Keywords: seven jumps; theory of planned behavior; prevention of sexual behavior ABSTRAK Latar belakang: Perilaku seksual makin marak di lingkungan remaja dengan berbagai akibat yang ditimbulkannya, salah satu nya adalah kehamilan remaja. Kurangnya informasi dan pemahaman yang salah tentang perilaku seksual yang mereka dapat dari berbagai media, mencoba dan berakibat buruk. Berbagai metode dilakukan untuk memberikan pemahaman kepada para remaja, salah satunya dengan pembelajaran metode seven jumps, belajar berdasarkan masalah dengan memperhatikan beberapa aspek latar belakang yang mempengaruhi terjadinya perlaku tersebut. Penelitian ini bertujuan untuk mengembangkan pembelajaran metode seven jumps berbasis Theory of Planned Behavior (TPB) terhadap pencegahan perilaku seksual pada remaja putri di SMK dr Soetomo Surabaya. Metode: Jenis penelitian analitik observasional, desain cross sectional. Populasi penelitian remaja putri kelas XII dan kelas XI di SMK dr Soetomo Surabaya, besar populasi 320. Besar sampel dalam penelitian ditentukan dengan rumus Rule of the Thumb, besar sampel 210 siswa. Variabel independen dalam peneliian ini adalah seven jumps; theory of behavior planned dan pencegahan perilaku seksual merupakan variabel dependen. Pengumpulan data menggunakan kuesioner. Analisis data secara deskriptif dan analisis inferensial dengan PLS (Partial Least Square) (faktor loading ≥ 0.5 dan t > 1.96). Hasil: ada pengaruh faktor sosial terhadap perceived behavior control, faktor personal terhadap attitude toward behavior, faktor personal terhadap perceived behavior control, faktor personal terhadap subjective norm, faktor information terhadap attitude toward behavior, faktor information terhadap perceived behavior control, attitude toward behavior terhadap seven jumps, perceived behavior control terhadap seven jumps, subjective norm terhadap seven jumps, seven jumps terhadap intention perilaku seksual (t ˃ 1.96), dan tidak ada pengaruh faktor sosial terhadap subjective norm, faktor sosial terhadap attitude toward behavior information terhadap subjective norm (t ≤ 1.96) Kesimpulan: variabel latar belakang faktor personal, faktor sosial dan faktor informasi berpengaruh terhadap ke tiga variabel attitude behavior control, norma subyektif dan perceived behavior control, sedangkan ke tiga variabel tersebut akan mempengaruhi pelaksanaan metode seven jumps, dan seven jumps berpengaruh terhadap intense pencegahan perilaku seksual. Kata kunci: seven jumps; theory of behavior planned; pencegahan perilaku seksual